The Influence Of Big Five Personality, Coping Stress And Demographic Variables On Post Traumatic Growth In Adolescents - Noffa Iffayanti; Natris Idriyani (‎‎‎TAZKIYA Journal of Psychology, 2017)
This study was conducted to determine the significance of big five personality, coping stress and demographic variables on post traumatic growth in adolescents who lost one parent (Orphans) in five orphanages around Jakarta. Subjects in this study amounted to 232 orphaned teenagers living in orphanages in the Jakarta area, which was taken with nonprobability sampling technique that is purposive sampling. CFA (Confirmatory Factor Analysis) is used to test the validity of measuring instruments and Multiple Regression Analysis is used to test the research hypothesis. The results showed that there was a significant effect together from big five personality, coping stress and demographic variable (gender) to post traumatic growth in adolescent orphanage. Hypothesis test results from big five personality variable dimension show that personality type of openness has a significant influence on post traumatic growth. The results also show the proportion of variance ofpost traumatic growth described by all independent variables is 9.2%, while the rest is influenced byother variables outside this study. DOI: 10.15408/tazkiya.v22i1.8162